Implementasi Kebijakan Kurikulum Mardeka di Sekolah Dasar Negeri 03 Lubang Panjang Kota Sawahlunto - Ermida; Fadriati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to determine the implementation of the independent curriculum policy based on Permendikbud number 3 of 2020 at State Elementary School 03 Lubang Panjang, Sawahlunto City. The research method used is library research (library study) with qualitative methods. Secondary data sources come from 33 national journal articles as well as observations at the school. Data collection methods are observation and documentation methods. The data analysis technique consists of four stages, namely data collection, data reduction, data presentation, and inference. The results of several researchers found that the independent learning curriculum has been implemented at SD Negeri 03 Lubang Panjang, Sawahlunto City, and the independent learning curriculum policy has been implemented even though it requires several improvements and developments. However, the implementation of the Independent Campus Learning policy encourages the learning process at the school to become more autonomous and flexible. Education always strives to create students who always make updates all the time. Not only great in the knowledge department, but also able to become students who are innovative, creative and productive, and can carry out the resulting innovations which can make a maximum contribution to the progress of a nation that has quality human resources